Succesfulness of Controlling and Prevention of Leprosy in Aceh Tenggara Regency, Indonesia (Indonesian Journal of Pharmaceutical and Clinical Research, 2022)
Leprosy remains as a health problem in Indonesia. This retrospective descriptive study analyzed the succesfulness of controlling and prevention of leprosy by Deparment of Health Aceh Tenggara Regency (DHATR), Indonesia period 2010 to 2019. The required data (n=125) were extracted from the DHATR databases using a self-designed questionnaire. The new cases, grade 2 disability  rate, recovery rate with  multi-drug therapy (MDT), isolation measures for leprosy patients, bacille calmette-guerin (BCG)  vaccination for the patients’ families, and tertiary prevention were analyzed using a cohort analysis. Succesfulness of the program was analyzed by referring the study results  with the National Guidelines for Eradicating Leprosy (NGEL). Of the 125 patients, 62.4% were male. The new cases found for period: 2010 to 2016, > 5/100,000 population; 2017 to 2019, < 5/100,000 population. The incidence of level 2 disability period 2010 to 2019 was less than 25 cases/10 years and recovery in paucibacillary leprosy (PBL) and multibacillary leprosy (MBL) from 2010 to 2019 reached 100%. The incidence of MBL was higher than that of PBL at the age range of 1 to 70 years.There was no patients isolated and vaccinated during that period. The controlling and prevention  of leprosy in DHATR was in accordance with the NGEL.